Experience in obtaining and cryopreserving semen of Mid-Caucasian Tur, Capra Caucasica Güldenstaedt et Pallas, 1783 - Marina I. Selionova; Ali-Magomet M. Aybazov; Evgeniya S. Latynina (Caspian Journal of Environmental Sciences)
The study was primarily aimed at determining the possibility of preserving the quality parameters and functional value of the semen of Caucasian tur, Capra caucasica after cryopreservation. For this purpose, the following objectives were set: to find out the possibility of obtaining the semen of Caucasian tur by electroejaculation and to study the parameters of its fresh undiluted semen; to study the cryoprotective properties of the experimental synthetic medium for dilution of its semen; to study the quality parameters and functional value of the frozen semen; and to evaluate the fertilizing capacity of the frozen and thawed semen. In the field study, semen was obtained during the breeding season (late November) from three mature turs by electroejaculation. A total of 19 ejaculates were obtained and evaluated. At each retrieval, ejaculates were pooled to exclude the influence of individual male characteristics and separated into two equal aliquots. One aliquot was then diluted with TRIS-based synthetic medium (control medium) and the other was diluted with the same medium supplemented with 10% platelet-rich plasma (PRP) from the same animal from which the biomaterial had been collected. Subsequently, all samples were cryopreserved in liquid nitrogen. The volume, total motility, velocity of sperm, acrosome, and plasma membrane integrity of sperm at different stages of cryopreservation (after dilution, equilibration, and freezing and thawing) were investigated. The results have shown that the semen obtained by electroejaculation had an average volume of 0.8 mL (range 0.3 to 1.4 mL), satisfactory quality parameters (sperm velocity 76% (7.6 points on a 10-point scale), average concentration 2.85 × 108 sperms mL-1). Semen diluted with the experimental medium supplemented with 10% PRP had significantly higher total motility (p < 0.05) compared to the control medium after equilibration and freezing, and thawing. In the experimental diluent after freezing and thawing, the percentage of sperm with high motility has significantly increased (p < 0.05) compared to the control medium. The addition of 10% PRP resulted in improved progressive motility and viability of sperm after cryopreservation (p < 0.05), as well as increased acrosome preservation and plasma membrane integrity compared to the control medium. The fertilizing ability of cryopreserved semen frozen in the experimental medium was 19.1% higher compared to the control medium.